Study on Analysis Methods of Power Quality Economic Cost Oriented End-users - 甄晓晨; 陶顺; 肖湘宁 (Kongzhi Yu Xinxi Jishu)
Power quality problems can cause enormous economic losses to electricity consumers. Based on a number of studies and articles, this paper presents a general overview of methods and processes to quantify economic impact of power quality problems. It also introduces in detail several ways to collect power quality economic data. Moreover, Net Present Value (NPV) method is introduced here to access power quality solutions. At last, the study scheme of power quality economic losses is proposed based on China’s actual conditions.